Detection of serum antibodies to tick-borne and other infections in patients with lymphadenopathy - M. A. Andreichyn; M. T. Huk; M. I. Shkilna; K. B. Shtokailo; M. M. Korda (Zaporožskij Medicinskij Žurnal)
The aim was to determine the prevalence of serum antibodies to tick-borne pathogens and other infectious agents in patients with lymphadenopathy.